COMPARATIVE ANALYSIS OF PHRASEOLOGICAL UNITS IN ENGLISH, UZBEK AND RUSSIAN LANGUAGES - Kambarova Marjan Adil kizi (Western European Studies, 2025)
A phraseological unit refers to a fixed or semi-fixed expression, phrase, or combination of words whose meaning is not directly derived from the individual meanings of the words that make it up. These expressions often have a specific, idiomatic meaning that cannot be easily guessed based on the words alone. In linguistics, these units are important because they show how language can develop rich, culturally embedded ways of conveying meaning beyond simple word-for-word translation. They include idioms, proverbs, collocations, and other expressions that are often used in everyday speech or writing.
Keywords: phraseology; a phraseological unit; free-word groups